Synthesis, neutron diffraction study and cation substitutions in Srn-1Cun+1O2n (n=3,5) - Kazakov, S; Pachot, S; Kopnin, E; Putilin, SN; Antipov, E; Chaillout, C; Capponi, J; Radaelli, P; Marezio, M (1997)
The n = 3 and n = 5 members of the homologous series Srn-1,Cun+1O2n have been synthesised by a high-pressure, high-temperature technique and characterized by X-ray powder diffraction and electron microscopy as well as EDS microanalysis. The solubility range of Sr4-xNdxCu6O10 solid solution was found to be <0.1. The crystal structure of Sr4Cu6O10 was refined from neutron powder diffraction data.